Can we reposition finite element human body model like dummies? - Tang, Jisi; Zhou, Qing; Shen, Wenxuan; Chen, Wentao; Tan, Puyuan (Frontiers in Bioengineering and Biotechnology, 2023)
How to rapidly reposition Finite Element Human Body Models (FE-HBMs) with high biofidelity is an important but notorious problem in vehicle safety and injury biomechanics. We propose to reposition FE-HBM in a dummy-like manner, i.e., through pose parameters prescribing joint configurations. Skeletons are reconfigured along the trajectories inferred from model-specific bone geometries. We leverage differential geometry to steer equidistant moves along the congruent articulated bone surfaces. Soft tissues are subsequently adapted to the reconfigured skeletons through a series of operations. The morph-contact algorithm allows the joint capsule to slide and wrap around the repositioned skeletons. Nodes on the deformed capsule are redistributed following an optimization-based approach to enhance element regularity. The soft tissues are transformed accordingly via thin-plate spline. The proposed toolbox can reposition the Total Human Body Model for Safety (THUMS) in a few minutes on whole-body level. The repositioned models are simulation-ready, with mesh quality maintained on a comparable level to the baseline. Simulations of car-to-pedestrian impact with repositioned models exhibiting active collision-avoidance maneuvers are demonstrated to illustrate efficacy of our method. This study offers an intuitive, effective and efficient way to reposition FE-HBMs. It benefits all posture-sensitive works, e.g., out-of-position occupant safety and adaptive pedestrian protection. Pose parameters, as an intermediate representation, join our method with recently prosperous perception and reconstruction techniques of human body. In future, it is promising to build high-fidelity digital twin of real-world accidents using the proposed method, and investigate human biomechanics therein, which is of profound significance to reshaping transportation safety study in future.